2016
DOI: 10.1111/cdev.12509
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Infant Attention: Implications for Crossmodal Perception and Word‐Mapping Research

Abstract: The present review is a novel synthesis of research on infants' attention in two related domains-crossmodal perception and word mapping. The authors hypothesize that infant attention is malleable and shifts in real time. They review dynamic models of infant attention and provide empirical evidence for parallel trends in attention shifts from the two domains that support their hypothesis. When infants are exposed to competing auditory-visual stimuli in experiments, multiple factors cause attention to shift duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 141 publications
(181 reference statements)
0
10
0
Order By: Relevance
“…These findings underscore the role of language experience in shaping the timing and flexibility of perceptual narrowing to one noun-friendly language versus two. In addition, they underscore that infants utilize general-purpose (Gogate, 2016; Gogate & Maganti, 2016), perceptual narrowing or protraction, and auditory-visual synchrony perception mechanisms to learn word-action relations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings underscore the role of language experience in shaping the timing and flexibility of perceptual narrowing to one noun-friendly language versus two. In addition, they underscore that infants utilize general-purpose (Gogate, 2016; Gogate & Maganti, 2016), perceptual narrowing or protraction, and auditory-visual synchrony perception mechanisms to learn word-action relations.…”
Section: Discussionmentioning
confidence: 96%
“…As these infants naturally learned more words, in particular, nouns in the noun-friendly language (e.g., English) as per maternal report on the MacArthur-Bates Communicative Development Inventories (MCDI, Fenson, Dale, Reznick, Bates, Thal & Pethick, 1994), their verb-action mapping in the laboratory was attenuated relative to infants who had not learned as many nouns. Thus, tuning into a noun bias and learning more novel noun-object relations results in a temporary perceptual-lexical narrowing to nouns which, in turn, temporarily attenuates word-action mapping in postverbal relative to preverbal infants: the perceptual-lexical narrowing hypothesis (Gogate & Hollich, 2016; Gogate & Maganti, 2017). Substantiating this hypothesis, the postverbal 12- to 14-month-old infants failed to learn two novel word-action mappings when exposed to the pairings during habituation, whereas the preverbal 8- to 9-month-old infants succeeded in learning these mappings (Gogate & Maganti, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, some recent studies also employ infant-controlled trials (e.g., see Gogate & Maganti, 2017;Hay et al, 2015;Singh et al, 2014 in which the trial terminates if infants look away from the display for a certain amount of time (usually 1 or 2 sec). Although we are not aware of any studies which directly suggest that fixed-time trials and infant-controlled trials in the habituation phase yield different looking behaviors in the test phase (but see Gogate & Maganti, 2016 for a detailed review of the dynamics of infant attention shift), it is possible that this methodological difference may contribute to the result we obtained in this study. Further, in lieu of using isolated speech tokens from one particular speaker as auditory stimuli as in the present study, using stimuli by multiple talkers (Rost & McMurray, 2010) or embedding target words in naming phrases (Fennell & Waxman, 2010) may facilitate word learning using pitch accent in 14-month-old infants.…”
Section: Discussionmentioning
confidence: 92%
“…Thus vowels may act as better perceptual and attentional attractors. Previous studies showed that attention benefits word-object learning during early infancy 30 . In our study, allocating the attention to the salient parts of the speech component of the audiovisual stream may benefit the segmentation of the stream, the discovery of the words, and consequently, the encoding of the word-image associations.…”
Section: Discussionmentioning
confidence: 96%